2021
DOI: 10.1111/ens.12460
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of the ectomycorrhizal fungi Rhizopogon roseolus and R. luteolus by Chamaesyrphus japonicus (Diptera: Syrphidae)

Abstract: In spite of the uniform flower feeding habitat of adult hoverflies, their larval feeding ecology is diverse. The genus Chamaesyrphus Mik, 1895, is rare and its larval feeding ecology is entirely unknown. Here we reported larval feeding ecology of Chamaesyrphus japonicus Shiraki, 1956. We found that nine larvae of Cha. japonicus fed on five fruitbodies of ectomycorrhizal hypogeous basidiomycete fungi Rhizopogon roseolus (Corda) Th. Fr., Svensk, 1909, while two larvae of Cha. japonicus fed on two fruitbodies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…The rearing process found that the pupae is the overwintering developmental stage. Okada et al (2021) reported that the Pelecocera japonica larvae they found dwelled in the liquefied decaying inner tissue (gleba) of the specimens of Rhizopogon spp. The larvae of P. tricincta and P. caledonica here reported from Rhizopogon luteolus fruit bodies were likewise only found in liquefied fungal tissue of olive-brown colour and with an oily viscosity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rearing process found that the pupae is the overwintering developmental stage. Okada et al (2021) reported that the Pelecocera japonica larvae they found dwelled in the liquefied decaying inner tissue (gleba) of the specimens of Rhizopogon spp. The larvae of P. tricincta and P. caledonica here reported from Rhizopogon luteolus fruit bodies were likewise only found in liquefied fungal tissue of olive-brown colour and with an oily viscosity.…”
Section: Discussionmentioning
confidence: 99%
“…Speight (2020) ). Recently Okada et al (2021) confirmed mycophagy as the feeding mode of Pelecocera ( Chamaesyrphus ) japonica . They observed larvae in fungal fruit bodies of Rhizopogon roseolus (Corda) Th.…”
Section: Introductionmentioning
confidence: 95%
“…Invertebrates can carry spores on their legs or in their intestines [ 38 , 126 , 127 ]. Guyanagaster necrorhizus (Agaricales, Agaricomycetes) spores adhere to the exoskeleton of termites in the genera Cylindrotermes , Dihoplotermes , and Nasutitermes [ 128 ] Several studies show that especially Diptera are adept at carrying viable fungal spores in their intestines [ 39 , 129 , 130 , 131 ]. These spores retain the ability to form mutualistic associations with plants [ 40 , 126 ] or infect organisms [ 132 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this idea has not been formally tested or proven. For example, contrary to this hypothesis, species of Rhizopogon and Suillus (Boletales, Agaricomycetes) have generally thin-walled, smooth, and hyaline spores yet with high rates of viability [ 131 , 134 , 135 , 136 , 137 ]. One final note to consider here is that invertebrates may be more efficient in spore dispersal compared to many mammals [ 125 ]…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of P. pruinosomaculata in either spring or autumn may be because these sites may be unfavourable for the species at one of these seasons. It was shown recently that Pelecocera japonica larvae feed on the fruit bodies of the basidiomycete Rhizopogon (Okada et al 2021). European species of Rhizopogon are associated with various species of Pinus trees (Molina & Trappe 1994).…”
Section: Discussionmentioning
confidence: 99%